Dynamic of Innovation in Services for Consumers at the Bottom of the Pyramid - Gibson Meira Oliveira; André Gustavo Carvalho Machado (BBR: Brazilian Business Review)
This paper aims to analyze the dynamic of innovation in services for consumers at the bottom of the pyramid (BoP). For this purpose, a framework composed of innovation dimensions, capabilities and infrastructure was developed. To assess the framework behavior in the business practice, a case study was carried out in a retail firm operating in Brazil’s Northeast region whose target consumers are at the BoP. The results showed adherence of the proposed framework to the dynamics of innovation conducted by the studied firm. Considering the theoretical- academic perspective, the framework helps explain the interaction between dimensions, capabilities, and elements of the market infrastructure. As for its practical relevance, it explains how service innovations occur and how to adapt them to the BoP market. In addition, as the structure of the proposed framework includes both external and internal elements, innovation is then considered from different perspectives.